An evaluation of the qualifications of selected academic law librarians in Metro Manila - Dadubo, Dave Virgel F.; Aguirre, Vyva Victoria M. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
This study evaluated the job performance of 36 selected law librarians from 14 academic and law school libraries in Metro Manila. They were evaluated based on three elements, namely: (1) the qualification requirements for the position they currently hold; (2) the actual qualifications they possessed; and (3) the performance of the duties and responsibilities assigned to them.
This study was aimed to : (1) determine the qualification requirements for law librarians employed in selected academic law libraries in Metro Manila; (2) establish a relationship between the qualification requirements of the position, the qualifications actually held by the law librarians, and the quality of their performance; and (3) determine whether or not special training in the field of law and/or law librarianship has had an influence in the law librarians' performance.
In addition to this study's objectives, it also sought to determine the problems encountered by the law librarians in the performance of their work. Law librarians who were actually employed and working in academic law libraries in Metro Manila were the target respondents. Evaluation of their performance was the primary method used to determine their actual job performance. Survey questionnaires, interviews and observations were the actual research techniques used to collect the needed information for the study. Data were analyzed using Statistical Package for Social Sciences (SPSS). In the study's results and findings, it was revealed that: qualification requirements such as being a licensed librarian, Library Science or Library and Information Science graduate, graduate of any degree, and having a Master's degree in Library Science or Library and Information Science were the most commonly required qualifications among the respondents; (2) the law lirarians' job performance will either be very satisfactory or satisfactory if they possessed educational qulifications such as a Bachelor or Master's degree in Library Science or Library and Information Science; (3) Majority of law librarians (80.6%) believed that a law degree is not necessary in their profession. However, they believed that good training programs, work experiences, and specialized education for law librarianship is more appropriate for their work; (4) problems experienced in dealing with library users, library's collection development, and in technical services were the problems most commonly encountered by the respondents in the performance of their duties.
From these results and findings, conclusions and recommendations were formulated to further develop and improve the law librarians' performance in the present time and in the future.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Librarians -- Philippines -- Manila Metropolitan Area; Law libraries -- Philippines -- Manila Metropolitan Area